The Influence of Implementing the Core Values of Achievement on Employee Work Productivity at The PTPN 1 Regional 7 Lampung - Khotimah, Nurul; Oktaviannur, M. (The Eastasouth Management and Business, 2025)
As an effort to strengthen the organizational culture of the Minister of BUMN, the Ministry of BUMN has set the core values of AKHLAK, which stands for Trust, Competent, Harmonious, Loyal, Adaptive, and Collaborative, to be applied throughout the scope of BUMN companies. This study aims to see the effect of the application of moral core values on employee work productivity at PTPN 1 Regional 7 Lampung. This study uses a quantitative method obtained from questionnaires. The population in this study is 426 employees of PTPN 1 regional 7 in Lampung, the determination of the sample in this study uses the slovin formula so that the number of samples taken is 81 respondents. The data analysis techniques used were instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis tests. From the results of data processing with SPSS version 26, it shows that the application of moral core values has an influence on employee work productivity at PTPN 1 Regional 7 Lampung.